2016
DOI: 10.1039/c6sc01808d
|View full text |Cite
|
Sign up to set email alerts
|

Stapled helical o-OPE foldamers as new circularly polarized luminescence emitters based on carbophilic interactions with Ag(i)-sensitivity

Abstract: Chiral stapled o-OPEs show excellent circular polarized luminescence responses (glum of 1.1 × 10–2) which can be modulated by carbophilic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 65 publications
5
54
0
Order By: Relevance
“…Theoretical calculations for ligand ( S , S )‐ 3 showed a preference for the coordination of Ag I cations with the three alkynes in a helical environment, as previously observed . Such arrangement forces coordination with a OMe group, and the configuration of the helix is inverted from ( S , S , M ) in the absence of Ag I to the ( S , S , P )‐ 3 :Ag complex.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Theoretical calculations for ligand ( S , S )‐ 3 showed a preference for the coordination of Ag I cations with the three alkynes in a helical environment, as previously observed . Such arrangement forces coordination with a OMe group, and the configuration of the helix is inverted from ( S , S , M ) in the absence of Ag I to the ( S , S , P )‐ 3 :Ag complex.…”
Section: Resultssupporting
confidence: 73%
“…We recently showed that folded o ‐OPE‐based nanopores could be filled with silver(I) cations through carbophilic interactions with alkynes, to give a new class of metallofoldamers (Figure , acyclic achiral organic emitters) . We also synthesized helical stapled o ‐OPEs with an enantiopure 2,3‐dihydroxybutane diether moiety, which showed excellent CPL responses (Figure , cyclic chiral enantiopure organic emitters) …”
Section: Introductionmentioning
confidence: 99%
“…By appropriate molecular design, the carbophilic interaction of Ag I can also act as the driving force to trigger the conformation changes and thus CPL switching for chiral fluorophores. This was well demonstrated by a Ag + ‐sensitive ortho ‐oligo(phenylene)ethylene (OPE) derivative p , p ‐ 13 (Figure ), which was reported by Cuerva and co‐workers. In compound 13 , the OPE can be fixed into a helical conformation .…”
Section: Cpl Switching By Changing the Conformationmentioning
confidence: 99%
“…With the idea to further enrich the photophysics of this fascinating platform we have built on their biaryl structure, which provides a means to arrive at dyes with helical chirality and the corresponding observation of interesting chiroptical properties, including the detection of circularly polarized luminescence (CPL) . The phenomenon is well established for supramolecular assemblies or nanostructures . However, the observation of CPL from small organic molecules (SOMs), albeit generally showing smaller dissymmetry factors ( g ), has recently created considerable interest in the dye chemistry community .…”
Section: Introductionmentioning
confidence: 99%